Inhibitory Effect of Ascorbic Acid on in vitro Enzymatic Digestion of Raw and Cooked Starches - Guo, Jiayue; Gutierrez, Alyssa; Tan, Libo; Kong, Lingyan (Frontiers in Nutrition, 2021)
Ascorbic acid, also known as vitamin C, was previously reported to inhibit the activity of pancreatic α-amylase, the primary digestive enzyme for starch. A major implication of such inhibition is a slowed rate of starch digestion into glucose, which thereby reduces postprandial hyperglycemia. The aim of this study was to explore the inhibitory effects of ascorbic acid at various concentrations on the in vitro digestion of high amylose maize starch (HAMS) and potato starch (PS) in both raw and cooked conditions. Resistant starch (RS) content, defined as the starch remained after 4 h of simulated in vitro enzymatic digestion, was measured for the starch samples. Upon the addition of ascorbic acid, the RS contents increased in both raw and cooked starches. Cooking significantly reduced the RS contents as compared to raw starches, and less increase in RS was observed with the addition of ascorbic acid. The inhibitory effect of ascorbic acid on the digestion of raw starches showed a dose-dependent trend until it reached the maximum extent of inhibition. At the concentration of 12.5 mg/mL, ascorbic acid exhibited the most potent inhibitory effect on the in vitro starch digestion in both raw and cooked conditions. Overall, our results strongly indicate that ascorbic acid may function as a glycemic modulatory agent beyond other important functions, and its effects persist upon cooking with certain concentrations applied.